SIGN ANALYSIS OF DISNEY MOVIE POSTER - Sari, Putu Widia Kumala; Maharani Santika, I Dewa Ayu Devi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to identify the verbal and non-verbal cues used in Disney movie posters as well as to interpret their significance. The verbal sign refers to text or words on the Disney movie poster. Colors and characters are used to represent non–verbal signs. The research data were taken from Pinterest. A descriptive qualitative method was used in this research. The theory from Saussure (2007), the denotation and connotation from Barthes in Chalder (2002), and the theory of color words from Wierzbicka (1996) were all applied in this research. The results of this research, Disney movie posters contained 6 non-verbal and 10 spoken signs. These meanings were found in the words and pictures of Disney movie posters.